Inquiry-Based Phase Change E-Module For Third Class Students - Dyah Triwahyuningtyas; Heni Widia Ayu Isnia; Novia Eka Mahmuda (Universitas Pendidikan Ganesha, 2022)
This research is motivated by the use of teaching materials in the form of worksheets, the material presented is less attractive so that it cannot be on time during the learning process. This affects the ability of students to think critically to solve material problems of change of form. This study aims to develop an inquiry-based e-module of transformation for grade 3 elementary school students. The subjects of the study were 10 grade 3 elementary school students. Development research methods using 4D models include Define, Design, Develop, and Disseminate. Intrument used in this study is questionnaire sheets. The data analysis used quantitative and qualitative techniques through media and material expert validators and teacher and student response questionnaires. The results showed that the inquiry-based phase change e-module was declared feasible or valid with an average score of 94.16% (Media Expert) and 82.36% (Material Expert). The use of e-modules through a questionnaire response of 92.75% of teachers and 84.79% of students was efficient. Therefore, it influences students' understanding of phase change material with an average value of 81. So that inquiry-based phase change e-modules can help students improve students contextual abilities foster students' cognitive and independent attitudes.